LANGUAGE TEACHER AGENCY IN FACING FREEDOM-TO-LEARN CURRICULUM IN TWO TOWNS IN JAVA - Putri, Maria Nirmala; Budiraharjo, Markus (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2024)
Teacher agency in facing new national curriculum shifts has been a topic discussed widely around the world, as many nations implement curriculum shifts and transitions. Indonesia has also in its early years implemented the new national curriculum called Freedom-to-Learn Curriculum. This study is aimed at exploring the agency of language teachers of public junior high schools in two different towns in Java Island, Indonesia. Employing the ecological approach by Priestley, Biesta, and Robinson (2015) which supported the interplay and dynamics of iterative, practical-evaluative, and projective dimensions, this qualitative study brings into play the semi-structured and focus group discussion data-gathering techniques. Six teachers participated in this study. The finding showed that the level of agency was diverse ranging from high (demonstrated by three research participants), emerging (demonstrated by one participant), and low (participated by two participants). Future researchers might examine the teacher agency by involving more participants as well as capture the robust study of language teacher agencies from other parts of Indonesia.